La semántica cognitiva y los esquemas-imagen en el sistema fitonímico de los jacaruhablantes - Escobar Zapata, Emérita (2015)
Our main purpouse is to interpret unpublished lexical data about botanic species from Tupe and Aiza (Yauyos, Lima), where the jacaru language is spoken today. After contrasting this written sources in fieldwork, we analyze them from a cognitive viewpoint as image schemas.